Ministerstwo Spraw Zagranicznych „Solidarności”. Biuro Koordynacyjne NSZZ „Solidarność”, 1982–1989, część 1 - Goddeeris, Idesbald; Błaszczyk, Katarzyna (Pamięć i Sprawiedliwość, 2006)
The proclamation of the Martial Law in Poland on 13 December 1981 caused a storm of protest in the West. Although some West European governments did not completely condemn Jaruzelski’s attempt to end the Polish crisis in an internal and ‘peaceful’ way, most Western societies reacted fi ercely on the delegalization of Solidarność, the arrest of thousands of its militants, and the return of repression. Dozens of committees were founded at both sides of the Atlantic Ocean by Western sympathizers, Polish migrants and even Solidarność members who were coincidentally kept abroad by the Martial Law. All these organizations tried to support the underground trade union in Poland by informing the public opinion of their country, lobbying at local and national authorities, and raising money to assist Polish victims and their families.In order to coordinate these actions, several umbrella organizations were set up. In many countries, Western trade unions created special forums on a national level. Polish migrants from their side, met in Zurich in December 1981 and in Brussels in January 1982, and decided that each country should have one coordinating offi ce. In some countries, this ambition of unifi cation was realized, but in other countries, ideological differences and personal tensions between local leaders were too big. Moreover, these committees could not be integrated by a Group of Delegates to the National Convention of the ISTU ‘Solidarity’ Currently Abroad, that was founded in Paris in February 1982 by delegates to the First (and only) National Congress of the NSZZ Solidarność (September 1981). However,when some leaders of the Polish underground created the Temporary Coordinating Commission (TKK) on 22 April 1982, and ordered their compatriots abroad to make a singlerepresentation in the West, a Coordinating Offi ce Abroad of NSZZ Solidarność (Biuro Koordynacyjne NSZZ Solidarność Za Granicą) was founded in Oslo in July 1982.At fi rst sight, the position of this Coordinating Offi ce looks very favorable. As it was created with the offi cial support of the TKK and was allowed to act as the offi cial intermediary between the leadership of Solidarność in Poland and foreign governments and institutions, it had an enormous advantage on most other exile organizations, that usually deal with problems of legitimacy, such as internal divisions and external recognition. Moreover, it could profi t from a very opportune climate: the events in Poland were followed in the West with a lot of attention and sympathy. However, the question presents itself whether these apparent trump cards were so permanent and useful as they seem to be on the faceof things. Could the Coordinating Offi ce indeed narrow the gaps between all the different groups within the Polish emigration? Was the Western support really that widely spread and that continuous? Were there differences between countries, ideological groups and types of partners the Coordinating Office collaborated with (e.g. trade unions, human rights organizations, national governments, international organizations…). Finally, wasthe Coordinating Offi ce able to profi t from the support and to convert it in real influence? And if so, on which fields, at which moments and to what extent could it get a grip on events? These are the main questions that will be dealt with in this article.